THE RUTHENIAN SILVER OF SOUTH-EAST UKRAINE IN THE TRANSLATIONS OF IBN BATTUTA’S NOTES (Південний архів (історичні науки), 2022)
The study analyzes an important fragment from the text of Ibn Battuta, which can be identified as relating to the south-east of Ukraine, which for a long time was absent in Russian language translations of memoirs. The purpose of the research is to find the facts from the history of Russia described by comparing Ibn Battuta’s translations, and to use the methods of related sciences to identify objects mentioned by the traveler as belonging to the south-east of Ukraine. The methods of research are based on a comparative analysis of the English translation of Ibn Battuta in the early 19th century. comparing it to Russian translations written at the same time. Having singled out the text that was “abbreviated” in the early Russian translations, we identify the areas described by the traveler thanks to the existing data on the geology of Ukraine. Results: 1) the silver ingots of the Ruthenians mentioned by Ibn Battuta (suwam), according to the description and the named weight correspond to the Kyiv hryvnia of the 12th–13th centuries; 2) the way of travel from the Tatar capital to the Azov and Tavria described by the traveler identifies the “Ruthenian Mountains” as an element of the landscape in the south-east of Ukraine; 3) the geological data allow further identification of these mountains as the Donets Ridge, according to information about silver deposits in the Donbas; 4) these facts, together with materials on the locations of the Crimea, were in one form or another omitted in Russian translations of memoirs. Conclusions: 1) the Kyiv hryvnia continued to be used in Ukraine in the 14th century. and was recognized in the Golden Horde; 2) silver deposits in Donetsk region could have been a source of Ruthenian silver mining, possibly in the past as well (minting of silver coins by Vladimir the Great); 3) the region was strongly associated with Ruthenia, the Tatars called it the “Ruthenians’ mountains”, belonging to, or associated with “their country”; 4) further research is required on why the excerpts regarding the weight of “suwam”, allowing to identify it as the Kiev hryvnia, were hidden for Russian language readers until 1884, and those on Saltuk the diviner, which show more details on Crimean and Azov geography and history of Muslim settlement, were changed in translation.
Keywords: Donbas, Donets Ridge, Crimea, memoirs, travelogue, Pryazovia